Large Right Atrial Vegetation in a Patient with Tunnelled Dialysis Catheter-Related Staphylococcal Sepsis : Remove the catheter if not in use - Prashanth Panduranga; Mohammed Al-Mukhaini (Sultan Qaboos University Medical Journal, 2013)
NA